Cell Therapy Based SARS-cov 2-2019 Managements: A Literature Review - Pourjabbar, Bahareh; Latifi, Parham; Soleimani, Masoud; Heidari keshel, Saeed; Jamaati, Hamidreza; Hashemian, Seyed Mohammadreza; Mortazavi, Seyed Mehdi (Regeneration, Reconstruction & Restoration (Triple R), 2020)
In early December 2019, an outbreak of coronavirus disease 2019 (COVID-19) occurred in Wuhan City, Hubei Province, China, affirmed to be the result of a novel coronavirus (later named Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)). Coronavirus disease-19, a kind of viral pneumonia, is caused by SARS-COV2. This virus infects angiotensin-converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) positive cells and causes influenza like symptoms ranging from mild disease to severe type with multi-organ involvement. In patients with more sever conditions, dysregulation of immune system, due to either virus activity or immune-based issues, leads to cytokine storm and unwanted inflammatory changes further followed by tissue damage. COVID-19 has spread rapidly by human-to-human transmission, caused an outbreak worldwide with considerable morbidity rates and mortality, which forced WHO to officially classified it as pandemic and a global concern on March 11. Without any signs of amelioration and with confirmed cases that are expected to increase further as they are updated daily as of May 8, the outbreak has stressed global socioeconomic and health systems and posed governments to clinical management challenges. Finding appropriate clinical strategy to control and even prevent is nowadays top priority issues globally. Recent studies and investigation considerably improve our understanding of disease pattern of distribution, pathology and immune-related changes in both mild and sever cases. Thus, many promising therapeutic approaches for clinical intervention and treatment of the disease are now under further investigations and their safety and efficiency are yet to be proved in clinical trials. One of these therapeutic approaches is cell therapy based interventions. Mesenchymal stem cells (MSCs) have commonly applied clinical trials and possess two positive roles, immunomodulatory effect and differentiation ability. MSCs immunomodulatory effects which mediated by anti-inflammatory cytokine release prevent or reduce the overactivation of the immune system and cytokine storm. So, MSCs therapy and other immune-based cell therapies can be promising in severe COVID-19 management and treatment. In this review the aim is investigation the impact of these kind of interventions in treatment of COVID-19 patients.